Clinical characteristics of Chinese patients with duration of type 2 diabetes >40 years: 病程40年以上的中国2型糖尿病患者的临床特点. (9th March 2016) - Song, Tingting; Luo, Yingying; Wang, Xuhui; Li, Jing; Han, Qian; Zhu, Hong; Zhao, Wei; Li, Weidong; Sun, Zhong; Yang, Xilin
Abstract: Background: Although type 2 diabetes mellitus (T2DM) shortens life expectancy by 10–12 years, some patients survive extremely long durations of diabetes. The clinical characteristics of Chinese patients with >40 years T2DM remain unknown. Thus, the aim of the present study was to document the clinical profile of patients with T2DM for ≥40 years. Methods: The present study evaluated 157 survivors with >40 years T2DM from a total of 582 773 patients with T2DM enrolled in a Chinese national survey of HbA1c. Two matched case‐control studies were performed on long T2DM survivors (cases) separately matched according to: (1) survey day, sex, and survey hospital; and (2) age, sex, and survey hospital. Conditional logistic regression analysis was performed to obtain odds ratios (ORs) for long survival. Results: Patients with a long duration of T2DM had a mean (± SD) age of 75 ± 10 years. Their T2DM had been diagnosed at a mean age of 32 years and the median duration of diabetes was 41 years. In both case‐control studies, long‐duration T2DM was associated with an increased risk of hyperglycemia (OR 6.31; 95% confidence interval [CI] 1.89–21.09) and coronary heart disease (CHD; OR 2.18 95% CI 1.01–4.70). However, long‐duration T2DM was not associated with a higher likelihood of abnormal lipids, diabetic nephropathy (DN), or stroke compared with patients with a shorter duration of T2DM. Conclusions: The present study suggests that Chinese patients with long‐term T2DM also had increased risks of hyperglycemia and non‐fatal CHD. Further studies are needed to investigate whether survival of these patients was associated with non‐increased risk of DN.